Morphological structures of rattan waste binderless particleboard: effect of acid treatment - T., Maisarah; A., Zuraida; H., Zahurin; I., Hanafi; Md. Abdul, Maleque (Microscopy Society Malaysia., 2015)
This study aims to investigate the effect of acid treatment on rattan fibers that used as raw material in manufacturing binderless particleboards. Acid treatment was done on rattan by boiling rattan in the diesel oil to prevent insects and fungi attacks. The rattan wastes gained from furniture manufacturing were used in manufactured binderless particleboards, and were analyses through scanning electron microscope (SEM). The manufactured boards had comparable strength properties. The treated structure of rattan fibers had rough surfaces without impurities, thinner and lighter in color compared to untreated structure of rattan fibers. The morphology of manufactured binderless particleboard demonstrated the compressed cellular structures with some voids and occurance of rattan skin. It can be concluded that acid treatment helps in improving interlocking between fibers inside binderless particleboard.